Patient, Defect, and Surgical Factors Influencing Use of Ancillary Procedures after Facial Mohs Repairs - Neuner, Romy A.; Sclafani, Anthony P.; Minkis, Kira; Obayemi, Ade; Navrazhina, Kristina; Cressey, Brienne; Ojeda, Sam; Trujillo, Oscar (Facial Plastic Surgery, 2021)
This article determines if patient, defect, and repair factors can be used to predict the use of additional treatments to achieve optimal aesthetic results after repair of facial Mohs defects. An electronic chart review of patients undergoing Mohs excision and reconstruction of facial neoplasms from November 2005 to April 2017 was performed, reviewing patient demographics and history, tumor size, defect size and location, method and service of reconstruction, time between resection and repair, complications, and subsequent treatments. A total of 1,500 cases with basal cell and squamous cell carcinoma were analyzed. The average defect size was 3.09 ± 8.06 cm2; 81.9% of defects were less than 4 cm2 in size. Advancement flaps were used to repair 44.3% of defects. Complications and undesired sequelae (CUS) were noted in 15.9% of cases; scar hypertrophy or keloid (10.8%) was most common. Postoperative ancillary procedures were performed in less than one-quarter (23.4%) of patients to enhance the postrepair appearance; the most common procedures were intralesional corticosteroid injections and pulse dye laser treatments. CUS were more likely in females (19.6%), defects on the lips (28.7%) and on the nose (27.3%) (p < 0.001 for each). Females (22.7% vs. 12.7%), lip repairs (40.2% vs. 18.3%), transposition flaps (39.2% vs. 14.8%), and repairs performed by a dermatologist (17.9% vs. 11.2%) (p < 0.001 for each) were more likely to be treated with postoperative corticosteroid injections. Females (14.5% vs. 7.4%), patients under the age of 60 years (13.9% vs. 8.8%), and patients whose repair was performed by a dermatologist (11.9% vs. 2.9%) (p < 0.001 for each) were more likely to receive postoperative pulsed dye laser treatments. CUS and ancillary procedures after repair of facial Mohs defects are uncommon. Awareness of individual risk factors and defect characteristics allows the surgeon to choose the most appropriate repair technique while anticipating the potential need for ancillary procedures.
Keywords: Mohs Defect; ancillary procedures; complications; scar revision; pulse dye laser